PENGARUH GOOD GOVERNANCE DAN TRANSFORMATIONAL LEADERSHIP TERHADAP EMPLOYEE PERFORMANCE DIMODERASI EMPLOYEE VOICE BEHAVIOR (STUDI KASUS PADA PT. ANGKASA PURA I (PERSERO)) - Aryanto, Asih; Etty Merawati, Endang; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2021)
The purpose of this study was to determine the effect of good governance, transformation leadership on employee performance and employee voice behaviour as a mediator variable. The population of this research is 186 people involved in the headquarter and big five Airport in PT. Angkasa Pura I (Persero). The number of samples of the population was 155 people taken using cluster sampling technique. The statistical method used in this study is Structural Equation Modeling (SEM) which is operated through the WarpPLS program. In this study, the results show that the variables of good governance, transformation leadership and employee voice behaviour have positive and significant influences on employee performance. employee voice behaviour as a mediator variable has positive and significant influences to encourage good governace on employee performance.